2003
DOI: 10.1202/396.1
|View full text |Cite
|
Sign up to set email alerts
|

Indoor Health: Background Levels of Fungi

Abstract: There is no uniformity in the suggested guidelines for acceptable levels of fungi in indoor ambient air. Thus, health professionals have no way to determine what levels of fungi may pose a threat to human health. The authors reviewed the published literature to identify data reported for noncomplaint structures, that is, structures in which occupants did not have health concerns associated with the quality of the indoor air. For both commercial and residential structures, fungal concentrations detected were of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 32 publications
1
14
1
Order By: Relevance
“…Unlike other studies that also found high levels of spores in different materials such as dust, surfaces or walls, the concentrations quantified in this work were already in the air, so all the spores are likely to be inhaled with the consequent increase in risk of causing health problems, while those that more or less adhered to a surface or other materials must pass to the air before they can penetrate the respiratory system (Gots et al 2003). As commented above, there are no standardised criteria to determine whether the values obtained fall within a range of high risk, but what we can say is that the concentrations registered are high enough to cause problems in human health, especially during the summer time, since the high peaks occur during the period of increased influx of visitors.…”
Section: Discussioncontrasting
confidence: 49%
See 1 more Smart Citation
“…Unlike other studies that also found high levels of spores in different materials such as dust, surfaces or walls, the concentrations quantified in this work were already in the air, so all the spores are likely to be inhaled with the consequent increase in risk of causing health problems, while those that more or less adhered to a surface or other materials must pass to the air before they can penetrate the respiratory system (Gots et al 2003). As commented above, there are no standardised criteria to determine whether the values obtained fall within a range of high risk, but what we can say is that the concentrations registered are high enough to cause problems in human health, especially during the summer time, since the high peaks occur during the period of increased influx of visitors.…”
Section: Discussioncontrasting
confidence: 49%
“…In fact, we found a wide range of values (Gots et al 2003;Baxter et al 2005) given by different organisations. Another problem is the difficulty of comparing the data obtained with other studies because of the use of different methods of sampling and the resulting presentation.…”
Section: Discussionmentioning
confidence: 92%
“…However, the connection between indoor mold and health-related complaints is still very much in contention. Gots et al (2003), for instance, have reported that a large range of fungal concentrations were measured even in non-complaint buildings.…”
Section: Introductionmentioning
confidence: 96%
“…The most frequent taxa are Cladosporium, Penicillium, Aspergillus, Alternaria, and Aureobasidium species. 1,2 Horner et al 3 estimated that of the 69,000 fungal species described to date, 4 only about 80 species have ever been identified as sources of allergens associated with allergic respiratory diseases mediated by IgE hypersensitivity. Studies of the aerobiology of allergenic fungi usually enumerate 10 to 20 of the more common genera, whereas the diagnosis of fungal allergy is usually made on the basis of responses to 3 or 4 species.…”
mentioning
confidence: 99%